Real-time Impact Evaluation of a Capacity-Building Health Project in Lao PDR - Kye Woo Lee; Tae Jong Kim (KDI Journal of Economic Policy, 2015)
This study presents a real-time impact evaluation of a human capacity building health project in Laos, financed by a Korean aid agency and executed jointly by Laotian and Korean higher educational agencies. The project aims to improve the health status of Laotians by enhancing practicing doctors' clinical performance capacity, to be attained by advancing academic achievement at the University of Health Sciences (UHS) in Laos. Therefore, this real-time impact evaluation adopted the difference-in-differences regression analysis method, showing that the project improved the academic achievement of the UHS students who were taught by the project fellowship awardees more, compared to the UHS students who were taught by non-fellowship faculty members. It remains to be evaluated whether these UHS students taught by the project fellowship recipients would also perform better clinically in public hospitals in the future.
Keywords: H43; H51; H52; H81; I15; I23; O15; O22; O53; 330; RealTime Impact Evaluation